2012
DOI: 10.1002/j.1532-2149.2012.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor consequences of experimentally induced limb pain: A systematic review

Abstract: Compelling evidence exists that pain may affect the motor system, but it is unclear if different sources of peripheral limb pain exert selective effects on motor control. This systematic review evaluates the effects of experimental (sub)cutaneous pain, joint pain, muscle pain and tendon pain on the motor system in healthy humans. The results show that pain affects many components of motor processing at various levels of the nervous system, but that the effects of pain are largely irrespective of its source. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 139 publications
(260 reference statements)
4
89
3
Order By: Relevance
“…Change in corticospinal excitability could be attributable to several causes. For example, patients with MSK disorders experienced pain for a prolonged period, and pain has been shown to exert an inhibitory effect over M1 (for reviews see (Farina et al, 2003;Mercier and Léonard, 2011;Bank et al, 2013)). It has recently been shown that even low pain levels are sufficient to induce such inhibition, and that the perceived pain level is not associated with the level of inhibition (Dubé and Mercier, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Change in corticospinal excitability could be attributable to several causes. For example, patients with MSK disorders experienced pain for a prolonged period, and pain has been shown to exert an inhibitory effect over M1 (for reviews see (Farina et al, 2003;Mercier and Léonard, 2011;Bank et al, 2013)). It has recently been shown that even low pain levels are sufficient to induce such inhibition, and that the perceived pain level is not associated with the level of inhibition (Dubé and Mercier, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3,28 While initially protecting an organism from harm, pain-related changes in movement can become maladaptive when they persist beyond recovery from the initial injury. 52 Pain-related adaptations in movement require a network architecture that allows for integration across pain and motor circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Second, increases in muscle strength resulting from resistance training may attenuate the loading forces experienced through the joint with weight-bearing activities. With fewer forces being absorbed by the joint resulting in less pain, activation of the a-motor neuron may be more coordinated because of lack of inhibition from the joint pain receptors, 37 resulting in more effective functional movements.…”
Section: Discussionmentioning
confidence: 99%